2020
DOI: 10.1080/1540496x.2020.1785864
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Firm-level Cash Holding—Moderating Effect of Goodwill and Goodwill Impairment

Abstract: The COVID-19 outbreak seriously affected all economies, especially the operations of listed companies, around the world. This article studies the impact of COVID-19 on firm-level cash holdings using the difference-in-differences method. It finds that COVID-19 has a significant positive impact on cash holdings in serious-impact industries. Goodwill and goodwill impairment can weaken this positive impact, which may be related to higher business risks in these firms. Therefore, managers should raise firms' cash h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 18 publications
6
62
0
17
Order By: Relevance
“… [6 , 12 , 13 , 14 , 17 , 23] . Present studies have also found that pandemics have impacted world economy across sectors to a greater extent negatively impacting the global outcome [21 , 24 , 26 , 29 , 32 , 36 , 39 , 40] . Among various sectors, pandemics have especially impacted global trade and financial sector negatively [15 , 18 , 31 , 34 , 38] .…”
Section: Introductionmentioning
confidence: 56%
“… [6 , 12 , 13 , 14 , 17 , 23] . Present studies have also found that pandemics have impacted world economy across sectors to a greater extent negatively impacting the global outcome [21 , 24 , 26 , 29 , 32 , 36 , 39 , 40] . Among various sectors, pandemics have especially impacted global trade and financial sector negatively [15 , 18 , 31 , 34 , 38] .…”
Section: Introductionmentioning
confidence: 56%
“…A major negative impact is related to firm performances [24]. Today many firms, especially small and medium enterprises (SMEs), are struggling to find survival plans for the next quarter or next month [25,26]. To survive in this turbulent environment, organizations must be agile with dynamic capabilities.…”
Section: Innovation Technology and Coronavirus: State Of The Artmentioning
confidence: 99%
“…In addition, this effect is pronounced under the lower level of gasoline production. COVID-19 negatively affects oil prices [2] , [23] , which in turn lead to lower level of gasoline production.…”
Section: Introductionmentioning
confidence: 99%